Sleep-Disordered Breathing Is Associated with Reduced Mandibular Cortical Width in Children. (January 2019) - Eimar, H.; Al-Saleh, M.A.Q.; Cortes, A.R.G.; Gozal, D.; Graf, D.; Flores-Mir, C.
Introduction: Evidence from the adult population suggests that sleep-disordered breathing (SDB) (i.e., obstructive sleep apnea [OSA]) is negatively associated with bone mineral density. Whether a similar association exists in children with SDB has not been investigated. Using the mandibular cortical width (MCW) as a proxy for skeletal bone density, we investigated if children at risk of SDB or diagnosed with OSA have a reduced mandibular cortical width compared to children without SDB. Methods: Two retrospective cross-sectional studies were performed. The first study included comparison of MCW between 24 children with polysomnographically (PSG) diagnosed OSA and 72 age- and sex-matched control children. The second study included a cohort of children in which SDB was suggested by the Pediatric Sleep Questionnaire (PSQ) ( n = 101). MCW was measured from panoramic radiographs. Results: Multiple-predictors regression analysis from the first study indicated that in children with a severe form of SDB, as induced by OSA severity, there was a negative association with MCW (β = –0.290, P = 0.049). Moreover, PSG-diagnosed OSA children had thinner MCW (2.9. ± 0.6mm) compared to healthy children (3.5 ± 0.6 mm; P = 0.002). These findings were further supported by the second study illustrating that PSQ total scores were negatively associated with MCW (β = –0.391, P < 0.001). Conclusions: Findings suggest that children at risk for or diagnosed with SDB exhibit reduced mandibular cortical width that purportedly may reflect alterations in bone homeostasis. Knowledge Transfer Statement: We report that sleep-disordered breathing (including its severe form, obstructive sleep apnea) in children is associated with reduced mandibular cortical width. This association might be a direct consequence of reduced bone health to sleep-disordered breathing or a reflection that reduced bone formation underlies the development of sleep-disordered breathing. Our findings suggest that mandibular cortical width can be used as an adjunct diagnostic parameter for the diagnosis of sleep-disordered breathing.